Encoding and Decoding in the field of Pragmatic - Ali, Sherzad (Humanities Journal of University of Zakho, 2020)
The code is a system of marks, consisting of (Encoding) and (decoding) and depends on the process of communication. This research Tries to study the components of the code, which are encoding and decoding in the field of Pragmatic, according to the descriptive-analytical approach. The research mainly aims to know what the role of Pragmatic in the process of encoding and decoding in the process of communication. The study consisted of an introduction and two chapters as well as the results. The first chapter which entitled by "Encoding" is generally focused on the encoding process and its types, and capabilities of the sender in the process of encryption and the role of Pragmatic in the formation of the code. The second chapter, entitled (Decoding), focuses on the abilities of the listener and the pragmatic role in deciphering the code.